Circuit mechanisms of GluA1-dependent spatial working memory - Freudenberg, Florian; Marx, Verena; Seeburg, Peter H.; Sprengel, Rolf; Celikel, Tansu (Hippocampus, 2013)
Spatial working memory (SWM), the ability to process and manipulate spatial information over a relatively short period of time, requires an intact hippocampus, but also involves other forebrain nuclei in both in rodents and humans. Previous studies in mice showed that the molecular mechanism of SWM includes activation of AMPA receptors containing the GluA1 subunit (encoded by gria1) as GluA1 deletion in the whole brain (gria1-/-) results in strong SWM deficit. However, since these mice globally lack GluA1, the circuit mechanisms of GluA1 contribution to SWM remain unknown. In this study, by targeted expression of GluA1 containing AMPA receptors in the forebrain of gria1-/- mice or by removing GluA1 selectively from hippocampus of mice with “floxed” GluA1 alleles (gria1fl/fl), we show that SWM requires GluA1 action in cortical circuits but is only partially dependent on GluA1-containing AMPA receptors in hippocampus. We further show that hippocampal GluA1 contribution to SWM is temporally restricted and becomes prominent at longer retention intervals (≥30 s). These findings provide a novel insight into the neural circuits required for SWM processing and argue that AMPA mediated signaling across forebrain and hippocampus differentially contribute to encoding of SWM. © 2013 Wiley Periodicals, Inc.